Substrate Temperature Influence on Optical Properties of C60 Thin Films Within the Visible Range - Jalaukhan, Ali H A; Hussein, Mustafa M A (Iraqi Journal of Science, 2019)
Fullerene thin films of about 200 nm thicknesses have been deposited by thermal evaporation method on soda lime glass at substrate temperature 303 and 403K under pressure about 10-5 mbar. This study concentrated on the influence of substrate temperature on the optical properties of C60 thin films within the visible range. Optical characterization has been carried out at room temperature using the absorption spectra, at normal incidence, in range (200-900) nm. The absorption and extinction coefficients of the samples have been evaluated according to the variation in the UV- Visible spectrum. Increasing substrate temperature causes decreasing in optical band gap energy, for direct allowed transitions, and slightly changing in refractive index. This incident was due to the reducing of interatomic intervals, which may be correlating a decrease in the amplitude of atomic vibrations around their equilibrium sites.